Correlates of Mental Depression Among Female Sex Workers in Southern India. (November 2015) - Patel, Sangram Kishor; Saggurti, Niranjan; Pachauri, Saroj; Prabhakar, Parimi
Mental health is an integral part of overall health status but has been a largely neglected issue in the developing world especially among female sex workers (FSWs). This study examines the prevalence and correlates of major depression among FSWs in southern India. Major depression was assessed using Patient Health Questionnaire-2 depression scale data from a cross-sectional Behavioral Tracking Survey, 2010-2011 conducted among FSWs (n = 1986) in Andhra Pradesh, a state in southern India. Almost two-fifths of FSWs (39%) reported major depression. Multivariate logistic regression analysis shows a significant association between major depression and the following characteristics for FSWs: low autonomy, alcohol use, experience of violence, police arrest, inconsistent condom use with clients, mobility for sex work, and being HIV positive or not wanting to disclose HIV status. Research and advocacy efforts are needed to ensure that the mental health issues of marginalized groups are appropriately addressed in HIV prevention programs.